THE EFFECT OF LOVING TOUCH STIMULATION THERAPY FOR INFANTS' WEIGHT GAIN - Malikhah, Fatatu; Widyawati, Melyana Nurul; Sutarmi, Sutarmi; Kistimbar, Siti; Taryatmo, Taryatmo; Kusmini, Kusmini (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Low Birth Weight (LBW) is one of the risk factors that have a high contribution to infant mortality. Increasing the baby's weight is used as an indicator to determine LBW growth. In LBW babies, touch therapy is a form of stimulation to increase endurance, digestive function activities, and vagus nerve activity. Objective: This study aims to determine the effect of Loving Touch Therapy (LTT) as one of the effective non-medical methods to increase body weight in LBW that can be done by parents during home care. Method: This study was a quantitative study using an experimental design and Randomized Controlled Trial (RCT) design. This research conducted in 15 respondents in the intervention group with four weeks' LTT and 15 respondents in the control group who were given Tactile Kinesthetic Stimulation (TKS). Data were obtained from measurements of body weight before and after the intervention then the data were analyzed using independent t-test with significance level p-value <0.05 and multivariate analysis using linear regression.Results: 19 respondents female (63.3%) and 11 respondents male (36.6%) was participated in this research by the frequency distribution of the gender. It was a significant increase in body weight in LBW with LTT carried out by his mother for 28 days compared with TKS stimulation. The differences in the average weight gain are 197 grams. The difference is statistically significant.Conclusions: It can be concluded that LTT is more effective in increasing body weight in LBW post-hospital care because the technique is simple and sequential from the front to the back of the baby's body which makes it easier for parents to understand and physiologically doesn't lose much an energy.